2004
DOI: 10.1016/j.mod.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila p24 homologues eclair and baiser are necessary for the activity of the maternally expressed Tkv receptor during early embryogenesis

Abstract: p24 proteins are assumed to play an important role in the transport of secreted and transmembrane proteins into membranes. However, only few cargo proteins are known that partially, but in no case completely require p24 proteins for membrane transport. Here, we show that two p24 proteins are essential for dorsoventral patterning of Drosophila melanogaster embryo. Mutations in the genes, eclair (eca) and baiser (bai), encoding two p24 proteins reduce signalling by the TGF-beta homologue, Dpp, in early embryos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…Our data on loj (Carney and Taylor, 2003) and CG31787 (Table 1), as well as previous work on the eca and bai genes (Bartoszewski et al, 2004), indicate that some widely expressed p24 genes have sex-specific functions; mutations in loj, eca, and bai have apparent phenotypic consequences only in females (Carney and Taylor, 2003;Bartoszewski et al, 2004). Because we have shown that particular p24 genes have developmental, tissue-specific, or transcript-specific expression patterns (Table 1; Fig.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our data on loj (Carney and Taylor, 2003) and CG31787 (Table 1), as well as previous work on the eca and bai genes (Bartoszewski et al, 2004), indicate that some widely expressed p24 genes have sex-specific functions; mutations in loj, eca, and bai have apparent phenotypic consequences only in females (Carney and Taylor, 2003;Bartoszewski et al, 2004). Because we have shown that particular p24 genes have developmental, tissue-specific, or transcript-specific expression patterns (Table 1; Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The developmental or tissue-specific profiles of p24 genes and proteins in multicellular organisms have not been extensively determined (Kawabe et al, 1999;Wen and Greenwald, 1999;Denzel et al, 2000;Kuiper et al, 2000;Rötter et al, 2002;Carney and Taylor, 2003;Bartoszewski et al, 2004). Because members of the p24 family may function together to provide different cargo or vesicle specificities (Marzioch et al, 1999;, an important first step in understanding their functions is to identify the p24 genes and proteins that are coexpressed within tissues.…”
Section: Three Drosophila P24 Genes Have Limited Expression Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…7C). p24 cycles between the ER and Golgi, is a major component of both COPII and COPI vesicles (50), serves as a primer for COPI vesicle formation (51,64), and, in isoform-specific fashion, appears to serve as a cargo receptor for glycosylphosphatidylinositol-anchored proteins (65,66), G-protein coupled receptors (67), and the Wnt ligand wingless (68,69). Proper p24 trafficking and interaction with other binding partners requires hetero-oligomerization among several closely related p24 family isoforms (70 -72).…”
Section: Alg-2/sec31a-prr Interactions Acutely Regulate Cargo Receptomentioning
confidence: 99%